Ecological response of some Iris L. taxa (Iridaceae) in Turkey - Kandemir, Nezahat; Çelik, Ali; Sürücü, Abdulkadir (Bangladesh Journal of Botany, 2012)
Ecological relationships of some Iris taxa belonging to subgenera Hermodactyloides (I. danfordiae, I. histrio subsp. aintabensis, I. histrio subsp. histrio, I. reticulata, I. bakeriana, I. pamphylica) and Scorpiris (I. aucheri and I. persica) have been compared and relationships between taxa have been determined. These taxa are geophytes and flower in Spring. I. danfordiae, I. pamphylica and subsp. aintabensis are endemic to Turkey. I. reticulata and I. persica have widespread distribution while I. aucheri, subsp. aintabensis, subsp. histrio, I. pamphylica and I. bakeriana have restricted distribution in Turkey. Soil samples of the taxa were collected during flowering periods and physical and chemical properties (texture class, total salinity %, pH, CaCO3 %, organic matter %, N %, P kg/da, K kg/da, Ca , Mg, Mn, Cu, Fe and Zn ppm) were determined. The correlations between the soil analyses and taxa were evaluated using regression analysis. The P and CaCOsub>3 values were found to be more effective than the other soil factors in the distributions of investigated taxa. Key words: Iris taxa; Endemic; Rare; Ecological properties; Relationship DOI: http://dx.doi.org/10.3329/bjb.v40i2.9774 Bangladesh J. Bot. 40(2): 177-184, 2011 (December)